Consumer credit: key aspects of Directive (EU) 2023/2225 and the challenge of responsible credit - Martín Pérez, José Antonio (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
Directive 2023/2225 updates the regulation of consumer credit agreements, aiming to correct the distortions generated by the transposition of the previous Directive, to strengthen the supply of cross-border credit, and improve consumer protection. To this end, the scope of application is broadened by adding new financing options, addressing the changes brought about by digitalization, and giving greater emphasis to creditworthiness assessments within the framework of responsible lending regulations. The Directive leaves sufficient options for Member States to shape consumer protection. The main challenge for national legislators will likely be to decide how to control interest rates to ensure they do not become „excessively high“, with the option of setting maximum limits.
Keywords: Consumer credit; EU Directive; consumer protection; responsible lending regulations